C.I. Pigment Yellow 101, Method For Producing Same, And Coloring Composition Containing C.I. Pigment Yellow 101
The particle size and crystal structure of C.I. pigment yellow 101 were adjusted by powder X-ray diffraction method, and the problem of reducing fluorescence color after small diameter was solved, and the effect of having high fluorescence color was achieved even if small diameter was small.
Patent Information
- Application Number
- CN202410503739.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-04-25
- Publication Date
- 2025-03-28
AI Technical Summary
When the C.I. pigment yellow 101 is reduced in diameter, the fluorescence color is easily reduced, and the prior art is difficult to maintain a high fluorescence color.
The particle size and crystal structure of C.I. pigment yellow 101 are adjusted by powder X-ray diffraction method to have an average particle size of 100 nm or more and 700 nm or less, and a second peak from the low angle side in the X-ray diffraction pattern exists within a specific range to reduce the change in the crystal structure.
Even during the pathization process, C.I. pigment yellow 101 can still maintain a high fluorescent color, avoiding the reduction of fluorescent color.
Smart Images

Figure CN119708876A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to CI Pigment Yellow 101, a method for producing the same, and a coloring composition containing CI Pigment Yellow 101. Background Art
[0002] Organic pigments are used as toners for electrophotographic image forming devices, and as color filters for liquid crystal displays, electronic paper, and organic EL displays. In recent years, the image quality required for high definition has also been improved. In this context, organic pigments are reduced in diameter for use in order to improve coloring power.
[0003] For example, Japanese Patent Application Laid-Open No. 2004-26930 discloses “an insoluble azo pigment having high crystallinity and a particle size of 30 to 150 nm”. Summary of the invention
[0004] However, when CI Pigment Yellow 101, which is a yellow organic pigment, is reduced in diameter, the fluorescent color may be impaired as the diameter is reduced.
[0005] An object of the present invention is to provide a CI Pigment Yellow 101 having a higher fluorescent color even with a smaller diameter than the following CI Pigment Yellow 101: having an average particle diameter of 100 nm or more and 700 nm or less, and having a second peak from the low angle side in an X-ray diffraction pattern obtained by a powder X-ray diffraction method in a range where the diffraction angle 2θ is less than 11.66° or more than 11.86°.
[0006] According to a first aspect of the present invention, there is provided a CI Pigment Yellow 101 having an average particle size of 100 nm or more and 700 nm or less, wherein in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low-angle side exists in the range of a diffraction angle 2θ=11.66° or more and 11.86° or less.
[0007] According to a second aspect of the present invention, the CI Pigment Yellow 101 based on the first aspect has an average particle size of 150 nm or more and 500 nm or less.
[0008] According to the third aspect of the present invention, in the CI Pigment Yellow 101 based on the first or second aspect, in the X-ray diffraction pattern obtained by powder X-ray diffraction, the third peak from the low angle side exists in the range of diffraction angle 2θ=17.86° or more and 18.06° or less.
[0009] According to the fourth aspect of the present invention, there is provided a method for manufacturing the CI Pigment Yellow 101 based on any one of the first to third aspects, comprising: using beads having a specific gravity of greater than 2.5 and less than 6.0 and a bead diameter of greater than 0.03 mm and less than 0.3 mm, and reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of greater than 1 μm and less than 5 μm under the condition that the peripheral speed of the stirring mechanism is greater than 4.8 m / s and less than 14.4 m / s.
[0010] According to a fifth aspect of the present invention, there is provided a coloring composition comprising the CI Pigment Yellow 101 according to any one of the first to third aspects.
[0011] According to a sixth aspect of the present invention, the coloring composition is a toner for developing an electrostatic charge image in the coloring composition according to the fifth aspect.
[0012] (Effect)
[0013] According to the first aspect, there is provided a CI Pigment Yellow 101 having a high fluorescent color even with a small diameter compared to the following CI Pigment Yellow 101: having an average particle diameter of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of less than 11.66° or more than 11.86°.
[0014] According to the second aspect, there is provided a CI Pigment Yellow 101 having a high fluorescent color even with a small diameter compared with a case where the CI Pigment Yellow 101 has an average particle diameter of 100 nm or more and less than 150 nm or more than 500 nm and less than 700 nm.
[0015] According to the third aspect, there is provided a CI Pigment Yellow 101 having a high fluorescent color even with a small diameter compared to the following case: in the case of CI Pigment Yellow 101, in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of greater than 11.66° and less than 11.86°, and in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the third peak from the low angle side exists in the range of a diffraction angle 2θ of less than 17.86° or greater than 18.06°.
[0016] According to the fourth aspect, there is provided a method for producing CI Pigment Yellow 101, wherein CI Pigment Yellow 101 has a high fluorescent color even when the diameter is small, compared with the following method for producing CI Pigment Yellow 101: comprising using beads having a specific gravity of less than 2.5 or greater than 6.0 or a bead diameter of less than 0.03 mm or greater than 0.3 mm, or reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of greater than 1 μm and less than 5 μm under the condition that the peripheral speed of a stirring mechanism is less than 4.8 m / s or greater than 14.4 m / s.
[0017] According to the fifth aspect, there is provided a coloring composition containing CI Pigment Yellow 101 having a high fluorescent color even with a small diameter, compared with the case of using the following CI Pigment Yellow 101: having an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of less than 11.66° or more than 11.86°.
[0018] According to the sixth aspect, there is provided a coloring composition which is a colorant for electrostatic image development and contains CI Pigment Yellow 101 having a high fluorescent color even when the diameter is small, compared with the case where the following CI Pigment Yellow 101 is used: having an average particle diameter of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of less than 11.66° or more than 11.86°. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram showing an example of an X-ray diffraction pattern of CI Pigment Yellow 101 according to the present embodiment obtained by a powder X-ray diffraction method. Figure 1 (A) is a schematic diagram showing an example of an X-ray diffraction pattern of CI Pigment Yellow 101 before particle size reduction, obtained by powder X-ray diffraction. Figure 1 (B) is a schematic diagram showing an example of an X-ray diffraction pattern of CI Pigment Yellow 101 after diameter reduction (Example) obtained by powder X-ray diffraction. Figure 1 (C) is a schematic diagram showing an example of an X-ray diffraction pattern of CI Pigment Yellow 101 after diameter reduction (comparative example) obtained by powder X-ray diffraction. DETAILED DESCRIPTION
[0020] The following describes embodiments of the present invention. These descriptions and examples are merely examples of the embodiments and do not limit the scope of the present invention.
[0021] In the present embodiment, a numerical range expressed using “to” indicates a range including the numerical values described before and after “to” as the minimum value and the maximum value, respectively.
[0022] In the numerical range of staged recording in the present embodiment, the upper limit or lower limit recorded in a numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range of recording in the present embodiment, the upper limit or lower limit of this numerical range can also be replaced by the value shown in the embodiment.
[0023] In the present embodiment, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0024] In this embodiment, when the embodiment is described with reference to the drawings, the structure of the embodiment is not limited to the structure shown in the drawings. In addition, the sizes of the components in each figure are only conceptual sizes, and the relative relationship between the sizes of the components is not limited to this.
[0025] In the present embodiment, each component may also include a plurality of suitable substances. In the present embodiment, when the amount of each component in the composition is mentioned, when there are a plurality of substances suitable for each component in the composition, when there is no special description, it refers to the total amount of the plurality of substances present in the composition.
[0026] In the present embodiment, the term "(meth)acrylic acid" means that it may be either "acrylic acid" or "methacrylic acid".
[0027] In the present embodiment, the term "fluorescent color" refers to the color of light having a wavelength of 510 nm to 530 nm (green).
[0028] <CI Pigment Yellow 101>
[0029] The CI Pigment Yellow 101 of the present embodiment is the following CI Pigment Yellow 101:
[0030] having an average particle size of 100 nm or more and 700 nm or less,
[0031] In the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low-angle side exists in the range of the diffraction angle 2θ=11.66° or more and 11.86° or less.
[0032] The CI Pigment Yellow 101 of the present embodiment has a high fluorescent color even when it has a small diameter due to the above-mentioned structure. The reason for this is presumably as follows.
[0033] CI Pigment Yellow 101 is a colorant that exhibits a fluorescent color.
[0034] On the other hand, the commercially available CI Pigment Yellow 101 has particles of about 3 μm, and when used in a coloring composition such as a toner, the particle size is reduced to improve the encapsulation property in the composition and the coloring property of the composition.
[0035] Here, as a method for reducing the diameter of an organic pigment, a mechanochemical method is widely used.
[0036] However, when CI Pigment Yellow 101 is reduced in diameter by the above method, the fluorescent color may be reduced.
[0037] As for the mechanochemical method, depending on the reduction method or the reduction conditions, sometimes a large mechanical energy is given to the organic pigment when the reduction is performed, which may cause lattice defects, lattice distortion, transformation of the crystal system and amorphization in the crystalline structure of the organic pigment. Therefore, it is believed that when CI Pigment Yellow 101 is reduced in diameter, the fluorescent color is reduced due to the change in the crystalline structure. The change in the crystalline structure can be confirmed by the change of the peak of the X-ray diffraction pattern obtained by the powder X-ray diffraction method of CI Pigment Yellow 101 after reduction in diameter to the high angle side (or low angle side).
[0038] In contrast, even if the diameter of CI Pigment Yellow 101 of the present embodiment is reduced, the second peak from the low angle side in the X-ray diffraction pattern obtained by the powder X-ray diffraction method exists in the range of diffraction angle 2θ=11.66° or more and 11.86° or less (see Figure 1 (B)). This indicates that the peak of the X-ray diffraction pattern obtained by the powder X-ray diffraction method in CI Pigment Yellow 101 after the reduction in diameter has less change to the high angle side (or low angle side) than before the reduction in diameter. That is, it is inferred that the change in the crystal structure of CI Pigment Yellow 101 after the reduction in diameter is less than that before the reduction in diameter, and the reduction in fluorescent color is suppressed.
[0039] From this, it is estimated that the CI Pigment Yellow 101 of the present embodiment has a high fluorescent color even if the diameter is small.
[0040] Next, the details of CI Pigment Yellow 101 according to the present embodiment will be described.
[0041] <CI Pigment Yellow 101>
[0042] The CI Pigment Yellow 101 of the present embodiment is 1,1′-[Azinobismethylidyne]bis[2-naphthol]. “CI” is an abbreviation for “Colour Index”.
[0043] The CI Pigment Yellow 101 of the present embodiment has an average particle size of 100 nm to 700 nm, and in an X-ray diffraction pattern obtained by powder X-ray diffraction, the second peak from the low angle side exists in the range of diffraction angle 2θ=11.66° to 11.86°.
[0044] The CI Pigment Yellow 101 of this embodiment has an average particle diameter of 100 nm to 700 nm, so it has a small diameter. The small diameter increases the specific surface area of the particles of CI Pigment Yellow 101, making it easier to absorb light and improve the coloring power.
[0045] On the other hand, from the viewpoint of preventing small-diameter particles (primary particles) of CI Pigment Yellow 101 from reaggregating with each other while maintaining the target tinting power and making it have a high fluorescent color, the average particle size of CI Pigment Yellow 101 is preferably from 150 nm to 500 nm, more preferably from 200 nm to 400 nm, and further preferably from 250 nm to 300 nm.
[0046] In addition, in the CI Pigment Yellow 101 of the present embodiment, in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low angle side exists in the range of diffraction angle 2θ=11.66° or more and 11.86° or less. By making the second peak from the low angle side not change significantly toward the high angle side (or the low angle side) and exist in the above range, the CI Pigment Yellow 101 has less change in crystal structure after the diameter is reduced than before. Therefore, the CI Pigment Yellow 101 of the present embodiment has a high fluorescent color even if it is small.
[0047] In the X-ray diffraction pattern obtained by the powder X-ray diffraction method of CI Pigment Yellow 101 of the present embodiment, the third peak from the low angle side is preferably present in the range of diffraction angle 2θ=17.86° or more and 18.06° or less. By making the third peak from the low angle side not change significantly to the high angle side (or low angle side) and exist in the above range, the change of the crystal structure of CI Pigment Yellow 101 after the diameter reduction is further reduced compared with before the diameter reduction. Therefore, CI Pigment Yellow 101 of the present embodiment is more likely to have a high fluorescent color even if it is small in diameter.
[0048] Here, in the X-ray diffraction pattern, each peak existing within the above-mentioned diffraction angle range 2θ means that the peak apex (the position with the highest peak intensity among the peaks existing within the above-mentioned diffraction angle range 2θ) exists within the above-mentioned diffraction angle range 2θ.
[0049] In addition, in the X-ray diffraction pattern obtained by the powder X-ray diffraction method of CI Pigment Yellow 101 of the present embodiment, the second peak from the low-angle side and the third peak from the low-angle side correspond to the peak at a diffraction angle of 2θ = 11.66° and the peak at a diffraction angle of 2θ = 17.86° in the X-ray diffraction pattern obtained by the powder X-ray diffraction method shown in Figure 4 of the non-patent literature (Xiang Yao, et al. "Multistimuli-Responsive Luminescence of Naphthalazine Based on Aggregation-Induced Emission" Chemistry Open Volume 4, Issue 4 p. 478-482), which are slightly shifted to the high-angle side.
[0050] <Method for producing CI Pigment Yellow 101>
[0051] The method for producing CI Pigment Yellow 101 of the present embodiment includes: using beads having a specific gravity of 2.5 to 6.0 and a bead diameter of 0.03 mm to 0.3 mm, under the condition that the peripheral speed of the stirring mechanism is 4.8 m / s to 14.4 m / s, reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of 1 μm to 5 μm, wherein CI Pigment Yellow 101 has an average particle diameter of 100 nm to 700 nm, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of 11.66° to 11.86°. By using a method using beads as a medium (i.e., a bead mill method) as a reducing method and performing reducing under the above conditions, CI Pigment Yellow 101 having a high fluorescent color even with a small diameter can be obtained.
[0052] Hereinafter, the details of the method for producing CI Pigment Yellow 101 according to the present embodiment will be described.
[0053] (Pre-process)
[0054] First, CI Pigment Yellow 101 to be reduced in diameter is prepared. As CI Pigment Yellow 101 to be reduced in diameter, a known commercial product can be used. The commercial product can be purchased from, for example, BASF Japan Co., Ltd., Neelicon Co., Ltd., and Radiant Co., Ltd. CI Pigment Yellow 101 to be reduced in diameter is used in advance with an average particle size of 1 μm or more and 5 μm or less from the viewpoint of reducing the diameter.
[0055] The CI Pigment Yellow 101 to be reduced in diameter is preferably in the form of a slurry immersed in a liquid. Examples of the liquid for preparing the slurry include water and tetrahydrofuran, and a surfactant or a dispersant may be used as necessary.
[0056] The slurry is preferably prepared so that the solid content concentration is, for example, 5 mass % or more and 30 mass % or less relative to the total mass of the slurry. Also, the slurry is preferably prepared so that the viscosity is, for example, 5 mPa·s or more and 500 mPa·s or less.
[0057] The slurry can be prepared by using a known stirring method such as a high-speed shearing disperser or a Henschel mixer.
[0058] (Small diameter)
[0059] Next, the slurry of CI Pigment Yellow 101 prepared above was added from the container inlet of the bead mill to reduce its diameter.
[0060] -Bead mill operating conditions-
[0061] The container of the bead mill can be vertical or horizontal.
[0062] The shape of the stirring mechanism of the bead mill can be appropriately selected from a disc type, a pin type, a single rotor, and the like.
[0063] The material of the beads may be appropriately selected from glass, alumina, high-purity alumina, zircon, zirconium oxide, silicon nitride, steel, and the like as long as it satisfies a predetermined specific gravity.
[0064] The specific gravity of the beads is 2.5 or more and 6.1 or less. By setting the specific gravity of the beads to the above range, excessive mechanical energy is not applied to CI Pigment Yellow 101 when the diameter is reduced, and CI Pigment Yellow 101 having a high fluorescent color can be obtained even with a small diameter. The specific gravity of the beads is preferably 3.0 or more and 5.0 or less, and more preferably 3.5 or more and 4.0 or less.
[0065] The method for measuring the specific gravity of beads is as follows.
[0066] Put 50g of beads into a 100mL measuring bottle. Next, use a 100mL measuring cylinder to measure 100mL of water. Then, add the measured water to the measuring bottle with beads until it reaches the mark on the measuring bottle, and calculate 50g / (volume of water remaining in the measuring cylinder) = specific gravity.
[0067] The bead diameter is 0.03 mm or more and 0.30 mm or less. By setting the bead diameter to the above range, the filling rate of the beads can be adjusted to a range where mechanical energy is less excessively applied to CI Pigment Yellow 101, and CI Pigment Yellow 101 having a high fluorescent color even with a small diameter can be obtained. The bead diameter is preferably 0.07 mm or more and 0.20 mm or less, and more preferably 0.10 mm or more and 0.15 mm or less.
[0068] The bead diameter is measured as follows.
[0069] The target beads were observed with an optical microscope and an image was taken. The image was input into an image analyzer (LUZEXIII, manufactured by NIRECO Co., Ltd.) for image analysis, and the equivalent circle diameter was calculated. Specifically, the area of each bead was measured, and the equivalent circle diameter was calculated based on the area value. The 50% diameter (D 50 ) was set as the bead diameter. Image analysis was performed on 200 randomly selected beads.
[0070] The filling rate of the beads is preferably 60% by volume or more and 95% by volume or less, more preferably 70% by volume or more and 90% by volume or less, and further preferably 75% by volume or more and 85% by volume or less, relative to the volume of the bead mill container. By setting the filling rate of the beads within the above range, mechanical energy is not excessively applied to CI Pigment Yellow 101, and CI Pigment Yellow 101 having a high fluorescent color even with a small diameter is easily obtained.
[0071] The peripheral speed of the stirring mechanism of the bead mill is 4.8m / s or more and 14.4m / s or less. By making the peripheral speed of the stirring mechanism the above range, mechanical energy will not be excessively applied to CI Pigment Yellow 101, and even if it is a small diameter, CI Pigment Yellow 101 with a high fluorescent color can be obtained. In addition, within the above range, the possibility of contamination caused by the heating of the slurry and the wear inside the mill is also small, so it is preferred. The peripheral speed of the stirring mechanism is preferably 6.0m / s or more and 13.2m / s or less, more preferably 7.2m / s or more and 12.0m / s or less, and further preferably 8.4m / s or more and 10.8m / s or less.
[0072] The residence time in the mill can be freely set to the time required for CI Pigment Yellow 101 to be reduced in diameter to a desired particle size, and is preferably 0.5 minutes to 15 minutes, more preferably 1 minute to 10 minutes, and even more preferably 1.5 minutes to 7.5 minutes.
[0073] - How a bead mill works -
[0074] The bead mill can be appropriately selected from batch type, pass type, and circulation type and operated.
[0075] (Post-process)
[0076] After the diameter reduction, the slurry of CI Pigment Yellow 101 is taken out from the container outlet of the bead mill and dried. The drying may be natural drying or reduced pressure drying.
[0077] By the above method, it is possible to produce CI Pigment Yellow 101 having a high fluorescent color even with a small diameter.
[0078] (Method for measuring physical properties of CI Pigment Yellow 101)
[0079] - Average particle size -
[0080] The average particle size of CI Pigment Yellow 101 can be calculated as follows.
[0081] The reduced diameter CI Pigment Yellow 101 is observed and imaged using a scanning electron microscope (SEM: Scanning Electron Microscope) device (S-4100, manufactured by Hitachi, Ltd.), and the image is input into an image analyzer (LUZEXIII, manufactured by Nireco Co., Ltd.) for image analysis, thereby being able to calculate.
[0082] Specifically, the area of each particle is measured, and the equivalent circle diameter is calculated from the area value. The 50% diameter (D 50 ) is defined as the average particle size of CI Pigment Yellow 101. Image analysis was performed on 200 randomly selected particles of CI Pigment Yellow 101.
[0083] - Diffraction angle 2θ of the peak in the X-ray diffraction pattern -
[0084] The diffraction angle 2θ of the peak in the X-ray diffraction pattern obtained by the powder X-ray diffraction method can be measured using an X-ray measuring device (Rigaku X-RAY DIFFRACTOMETER RINT-2100, manufactured by Rigaku Corporation). The measurement conditions are as follows.
[0085] X-ray source: CuK α
[0086] Sampling step width: 0.02°
[0087] Divergence slit: 1°
[0088] Scattering slit: 1°
[0089] Light receiving slit: 0.3mm
[0090] Voltage: 30kV
[0091] Current: 15mA
[0092] Measuring range: 5.0° to 35.0°
[0093] Step angle: 0.02°
[0094] Step time: 1.2 seconds
[0095] <Coloring composition>
[0096] The coloring composition of the present embodiment contains the CI Pigment Yellow 101 of the present embodiment.
[0097] The coloring composition of this embodiment is used for ink sheets for thermal transfer recording, toners for electrostatic image development (specifically, toner particles), inkjet recording inks, color filters, writing pens, colored plastics, other inks (such as paints), and the like.
[0098] The composition of this embodiment is particularly preferably used in an ink sheet for thermal transfer recording, a toner, and an ink for inkjet recording.
[0099] Next, as a representative application, a toner for electrostatic image development (specifically, toner particles) to which the composition of the present embodiment is applied will be described.
[0100] The electrostatic image developing toner (hereinafter also referred to as “toner”) of the present embodiment includes toner particles and, if necessary, an external additive.
[0101] (Toner particles)
[0102] The toner particles contain, for example, a binder resin and the CI Pigment Yellow 101 of the present embodiment. The toner particles may contain a colorant other than the CI Pigment Yellow 101 of the present embodiment, a release agent, and other additives as necessary.
[0103] Here, the content of CI Pigment Yellow 101 of the present embodiment is preferably 3% by mass or more and 10% by mass or less, and more preferably 5% by mass or more and 8% by mass or less, based on the entire toner particles.
[0104] - Adhesive resin -
[0105] Examples of the binder resin include homopolymers of monomers such as styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers.
[0106] As the binder resin, for example, non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosin, mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these resins can also be cited.
[0107] These binder resins may be used alone or in combination of two or more.
[0108] As the binder resin, polyester resin is preferable.
[0109] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can also be used together with a crystalline polyester resin. Among them, the crystalline polyester resin is preferably used in a content of 2% by mass or more and 40% by mass or less (preferably 2% by mass or more and 20% by mass or less) relative to the total binding resin.
[0110] The "crystallinity" of a resin means that it does not show a step-like change in endothermic value in differential scanning calorimetry (DSC) but has a clear endothermic peak. Specifically, it means that the half-value width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).
[0111] On the other hand, the "amorphous" nature of a resin means that the half value width exceeds 10°C, the endothermic value shows a step-like change, or a clear endothermic peak is not confirmed.
[0112] Amorphous polyester resin
[0113] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, commercially available products or synthetic resins may be used as the non-crystalline polyester resin.
[0114] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number is 1 or more and 5 or less) alkyl esters thereof. Among these, the polycarboxylic acid is preferably, for example, an aromatic dicarboxylic acid.
[0115] The polycarboxylic acid may also be used together with the dicarboxylic acid to form a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number of 1 to 5) alkyl esters.
[0116] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0117] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among them, the polyol is preferably, for example, an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0118] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylol propane, and pentaerythritol.
[0119] The polyols may be used alone or in combination of two or more.
[0120] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower.
[0121] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K 7121-1987 "Methods for determining transition temperatures of plastics".
[0122] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.
[0123] The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less.
[0124] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0125] In addition, the weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement based on GPC, GPC HLC-8120GPC manufactured by Tosoh is used as a measuring device, and a chromatographic column TSKgelSuperHM-M (15 cm) manufactured by Tosoh is used and THF solvent is used. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample based on the measurement results.
[0126] The amorphous polyester resin can be obtained by a known production method. Specifically, for example, the amorphous polyester resin can be obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as required, and reacting while removing water or alcohol generated during condensation.
[0127] In addition, when the monomer of the raw material is insoluble or miscible at the reaction temperature, a high boiling point solvent may be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is distilled off. In the case of the presence of monomers with poor compatibility, it is preferred to condense the monomers with poor compatibility with an acid or alcohol to be polycondensed with the monomers in advance, and then polycondense them together with the main component.
[0128] Crystalline polyester resin
[0129] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, or a synthetic resin may be used.
[0130] Here, in the case of the crystalline polyester resin, a polycondensate using a polymerizable monomer having a linear aliphatic group is more preferable than a polycondensate using a polymerizable monomer having an aromatic group in order to easily form a crystalline structure.
[0131] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., having a carbon number of 1 to 5) alkyl esters thereof.
[0132] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number of 1 to 5) alkyl esters.
[0133] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids.
[0134] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0135] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol. Among them, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.
[0136] The polyol may be used together with the diol in the form of a trivalent or higher alcohol having a cross-linked structure or a branched structure. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0137] The polyols may be used alone or in combination of two or more.
[0138] Here, the polyol preferably contains an aliphatic diol in an amount of 80 mol % or more, more preferably 90 mol % or more.
[0139] The melting temperature of the crystalline polyester resin is preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.
[0140] The melting temperature can be determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Methods for determining transition temperatures of plastics”.
[0141] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0142] The crystalline polyester resin can be obtained by a known production method, for example, similar to the amorphous polyester.
[0143] The content of the binder resin is, for example, preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and further preferably 60% by mass to 85% by mass, based on the entire toner particles.
[0144] - Colorants -
[0145] As a colorant, CI Pigment Yellow 101 of the present embodiment is included. Examples of the colorant that can be used in combination with CI Pigment Yellow 101 of the present embodiment include carbon black, chrome yellow, Hansa yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil-soluble red, pyrazolone red, lithotripter red, rhodamine B lake, lake red C, pigment red, Bengal rose red, aniline blue, ultramarine blue, calco oil blue, and the like. blue), methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate, titanium oxide, zinc oxide, calcium carbonate, basic lead carbonate, zinc sulfide-barium sulfate mixture, zinc sulfide, silicon dioxide, aluminum oxide and other pigments, or acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, thiazole-based and other dyes, etc.
[0146] Specific examples of the pigment include CI Pigment Yellow 1 (hereinafter referred to as “CI Pigment Yellow”).
[0147] So simplify the description and only record the numbers), 3, 11, 12, 13, 14, 15, 16, 17, 20, 24, 31, 53, 55, 60, 61, 65, 71, 73, 74, 81, 83, 86, 93, 95, 97, 98, 99, 100, 104, 106, 108, 109, 110, 113, 114, 116, 117, 119, 120, 125, 126, 127, 128, 129, 137, 138, 139, 147, 148, 150, 151, 152, 153, 154, 155, 156, 166, 167, 168, 175, 180, 185;
[0148] CI Pigment Orange 1 (hereinafter referred to as “CI Pigment Orange”, so the description is simplified and only the number is recorded), 5, 13, 14, 16, 17, 24, 34, 36, 38, 40, 43, 46, 49, 51, 55, 59, 61, 63, 64, 71, 73;
[0149] CI Pigment Violet 1 (hereinafter referred to as “CI Pigment Violet”, so the description is simplified and only the number is recorded), 19, 23, 29, 30, 32, 36, 37, 38, 39, 40, 50;
[0150] CI Pigment Red 1 (hereinafter referred to as "CI Pigment Red", so the description is simplified and only the number is recorded), 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 40, 41, 42, 48:1, 48:2, 48:3, 48:4, 49:1, 49:2, 50:1, 52:1, 53:1, 57, 57:1, 57:2, 58:2, 58:4, 60:1, 63:1, 63:2, 64:1, 81:1, 83, 88, 90:1, 97, 101, 102, 1 04, 105, 106, 108, 112, 113, 114, 122, 123, 144, 146, 149, 150, 151, 155, 166, 168, 170, 171, 172, 174, 175, 176, 177, 178, 179, 180, 185, 187, 188, 190, 192, 193, 194, 202, 206, 207, 208, 209, 215, 216, 217, 220, 223, 224, 226, 227, 228, 238, 240, 242, 243, 245, 254, 255, 264, 265;
[0151] CI Pigment Blue 1 (hereinafter referred to as “CI Pigment Blue”, so the description is simplified and only the number is recorded), 2, 15, 15:3, 15:4, 15:6, 16, 22, 60, 64, 66, 76;
[0152] CI Pigment Green 7, CI Pigment Green 36, CI Pigment Green 37, Pigment Green 58, CI Pigment Green 59;
[0153] CI Pigment Brown 23, CI Pigment Brown 25, CI Pigment Brown 26, CI Pigment Brown 28;
[0154] CI Pigment Black 1, CI Pigment Black 7, etc.
[0155] The coloring agent may be used alone or in combination of two or more.
[0156] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant. In addition, a plurality of colorants may be used together.
[0157] The content of the colorant is, for example, preferably 1% by mass or more and 30% by mass or less, and more preferably 3% by mass or more and 15% by mass or less, based on the entire toner particles.
[0158] - Release agent -
[0159] Examples of the release agent include hydrocarbon wax, natural wax such as carnauba wax, rice wax, candelilla wax, synthetic wax such as montan wax or mineral / petroleum wax, and ester wax such as fatty acid ester and montanic acid ester. The release agent is not limited thereto.
[0160] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower.
[0161] The melting temperature can be determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Methods for determining transition temperatures of plastics”.
[0162] The content of the release agent is, for example, preferably 1% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 15% by mass or less, based on the entire toner particles.
[0163] - Other additives -
[0164] Examples of other additives include well-known additives such as magnets, charge control agents, and inorganic powders. These additives are contained in toner particles as internal additives.
[0165] - Characteristics of toner particles, etc. -
[0166] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core-shell structure consisting of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.
[0167] Here, the toner particles of the core-shell structure preferably include, for example, a core portion including a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer including a binder resin.
[0168] The volume average particle size (D50v) of the toner particles is preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.
[0169] In addition, various average particle diameters and various particle size distribution indices of the toner particles were measured using a Coulter Multisizer II (manufactured by Beckman Coulter) and using ISOTON-II (manufactured by Beckman Coulter) as an electrolyte.
[0170] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and then added to 100 ml to 150 ml of the electrolyte.
[0171] The electrolyte solution in which the sample was suspended was dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size ranging from 2 μm to 60 μm was measured using a Coulter particle counter II with an aperture of 100 μm. The number of particles sampled was 50,000.
[0172] The cumulative distribution of volume and number of the particle size range (channel) divided based on the measured particle size distribution is plotted from the small diameter side, and the particle size with a cumulative value of 16% is defined as the volume particle size D16v and the number average particle size D16p, the particle size with a cumulative value of 50% is defined as the volume average particle size D50v and the cumulative number average particle size D50p, and the particle size with a cumulative value of 84% is defined as the volume particle size D84v and the number average particle size D84p.
[0173] Use them, by (D84v / D16v) 1 / 2 Calculate the volume particle size distribution index (GSDv) from (D84p / D16p) 1 / 2 Calculate the number average particle size distribution index (GSDp).
[0174] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0175] The average circularity of the toner particles is calculated by (equivalent circular circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.
[0176] First, the toner particles to be measured are sucked and collected to form a flat flow, and the particle image is captured as a still image by instantaneous stroboscopic light emission, and the particle image is analyzed using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). In addition, the number of samples for obtaining the average circularity is set to 3500.
[0177] When the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.
[0178] (External Additives)
[0179] Examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.
[0180] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment. The hydrophobic treatment is carried out, for example, by impregnating the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.
[0181] The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.
[0182] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin and other resin particles), detergent active agents (for example, metal salts of higher fatty acids represented by zinc stearate, and particles of fluorine-based high molecular weight bodies).
[0183] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.
[0184] (Method for producing toner)
[0185] Next, a method for producing the toner according to the present embodiment will be described.
[0186] The toner according to the present embodiment is obtained by manufacturing toner particles and then adding an external additive to the toner particles.
[0187] The toner particles may be produced by any of dry methods (eg, kneading and pulverization methods) and wet methods (eg, aggregation and coalescence methods, suspension polymerization methods, dissolution and suspension methods, etc.) The method for producing the toner particles is not particularly limited to these methods, and a known method may be used.
[0188] Among them, it is preferable to obtain the toner particles by an aggregation and coalescence method.
[0189] Specifically, for example, when toner particles are produced by an aggregation and coalescence method, the toner particles are produced through the following steps:
[0190] A process of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed and a colorant particle dispersion in which a colorant (specifically, CI Pigment Yellow 101 of the present embodiment) is dispersed (resin particle dispersion preparation process); a process of agglomerating resin particles and colorant particles (and other particles as needed) in a mixed dispersion of the resin particle dispersion and the colorant particle dispersion (in a dispersion after other particle dispersions are mixed as needed) to form agglomerated particles (agglomerated particle formation process); a process of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to fuse / agglomerate the agglomerated particles to form colorant particles (fusion / agglomeration process).
[0191] Hereinafter, the details of each step will be described.
[0192] In the following description, a method for obtaining toner particles containing a release agent is described, but the release agent is used as necessary. Of course, additives other than the release agent may also be used.
[0193] - Resin particle dispersion preparation process -
[0194] First, for example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared together with a resin particle dispersion in which resin particles serving as a binder resin are dispersed.
[0195] Here, the resin particle dispersion is prepared by, for example, dispersing the resin particles in a dispersion medium using a surfactant.
[0196] Examples of the dispersion medium used in the resin particle dispersion include aqueous media.
[0197] Examples of the aqueous medium include water such as distilled water and deionized water, and alcohols, etc. These may be used alone or in combination of two or more.
[0198] As surfactants, for example, anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols, etc. can be cited. Among them, anionic surfactants and cationic surfactants can also be specifically mentioned. Nonionic surfactants can also be used in combination with anionic surfactants or cationic surfactants.
[0199] The surfactant may be used alone or in combination of two or more.
[0200] As a method for dispersing the resin particles in the dispersion medium in the resin particle dispersion, for example, a general dispersion method such as a rotary shearing homogenizer, a ball mill with a medium, a sand mill, a dyno mill, etc. can be cited. In addition, depending on the type of the resin particles, for example, a phase inversion emulsification method can be used to disperse the resin particles in the resin particle dispersion.
[0201] In addition, the phase inversion emulsification method refers to the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (O phase) and neutralized, and then an aqueous medium (W phase) is added to thereby convert the resin from W / O to O / W (so-called phase inversion) without converting it to a continuous phase, so that the resin is dispersed in the aqueous medium in the form of particles.
[0202] The average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.
[0203] In addition, the average particle size of the resin particles is measured by using a particle size distribution obtained by a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), and the cumulative distribution of the volume is plotted from the small particle size side for the divided particle size range (channel), and the particle size at which the cumulative volume is 50% relative to all particles is measured as the average particle size D50v. In addition, the average particle size of particles in other dispersions is also measured in the same manner.
[0204] The content of the resin particles in the resin particle dispersion is, for example, preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less.
[0205] In addition, for example, a colorant particle dispersion and a release agent particle dispersion are prepared in the same manner as the resin particle dispersion. That is, the average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0206] - Agglomerated particle formation process -
[0207] Next, the colorant particle dispersion and the release agent particle dispersion are mixed with the resin particle dispersion.
[0208] Then, in the mixed dispersion, the resin particles, the colorant particles, and the releasing agent particles are heterogeneously aggregated to form aggregated particles having a diameter close to the diameter of the target toner particles and including the resin particles, the colorant particles, and the releasing agent particles.
[0209] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, a pH of 2 or more and 5 or less), and after adding a dispersion stabilizer as needed, the mixture is heated to a temperature of the glass transition temperature of the resin particles (specifically, for example, a temperature of the glass transition temperature of the resin particles of -30°C or more and the glass transition temperature of -10°C or less), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.
[0210] In the agglomerated particle formation step, for example, the above-mentioned coagulant can be added at room temperature (for example, 25° C.) while the mixed dispersion is stirred with a rotary shearing homogenizer, the pH of the mixed dispersion is adjusted to be acidic (for example, a pH of 2 or more and 5 or less), and the above-mentioned heating is performed after adding a dispersion stabilizer as needed.
[0211] As the coagulant, for example, a surfactant having a polarity opposite to that of the surfactant used as a dispersant added to the mixed dispersion, an inorganic metal salt, a divalent or higher metal complex can be cited. In particular, when a metal complex is used as a coagulant, the amount of surfactant used is reduced and the charging characteristics are improved.
[0212] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used. As such an additive, a chelating agent is preferably used.
[0213] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.
[0214] As the chelating agent, a water-soluble chelating agent may also be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).
[0215] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0216] - Fusion / agglomeration process -
[0217] Next, the aggregated particle dispersion containing the dispersed aggregated particles is heated to, for example, a temperature higher than the glass transition temperature of the resin particles (for example, a temperature 10 to 30° C. higher than the glass transition temperature of the resin particles) to fuse / agglomerate the aggregated particles to form toner particles.
[0218] Through the above steps, toner particles can be obtained.
[0219] In addition, the colorant particles can also be manufactured through the following steps: after obtaining an agglomerated particle dispersion in which agglomerated particles are dispersed, the agglomerated particle dispersion and a resin particle dispersion in which resin particles are dispersed are further mixed to agglomerate the resin particles in a manner that further adheres to the surface of the agglomerated particles to form second agglomerated particles; and the second agglomerated particle dispersion in which the second agglomerated particles are dispersed is heated to fuse / agglomerate the second agglomerated particles to form colorant particles with a core / shell structure.
[0220] Here, after the fusion / aggregation step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.
[0221] In the washing process, it is preferred to fully perform displacement washing using deionized water from the viewpoint of chargeability. In addition, the solid-liquid separation process is not particularly limited, and from the viewpoint of productivity, it is preferred to perform suction filtration, pressure filtration, etc. In addition, the drying process is not particularly limited, and from the viewpoint of productivity, it is preferred to perform freeze drying, air flow drying, fluidized drying, vibration-type fluidized drying, etc.
[0222] Then, the toner of the present embodiment is produced by, for example, adding an external additive to the obtained dry toner particles and mixing them. The mixing is preferably performed by, for example, a V mixer, a Henschel mixer, a Lödige mixer, etc. If necessary, a vibrating sieving machine, a wind sieving machine, etc. may be used to remove coarse particles of the toner.
[0223] <Electrostatic image developer>
[0224] The electrostatic image developer according to the present embodiment contains at least the toner according to the present embodiment.
[0225] The electrostatic charge image developer of the present embodiment may be a one-component developer containing only the toner of the present embodiment, or may be a two-component developer in which the toner and a carrier are mixed.
[0226] The carrier is not particularly limited, and known carriers may be cited. Examples of the carrier include a coated carrier in which a coating resin is coated on the surface of a core material composed of magnetic powder, a magnetic powder dispersed carrier in which magnetic powder is dispersed / blended in a matrix resin, and a resin impregnated carrier in which a porous magnetic powder is impregnated with a resin.
[0227] Furthermore, the magnetic powder dispersed carrier and the resin impregnated carrier may be a carrier in which the constituent particles of the carrier are used as a core material and the core material is coated with a coating resin.
[0228] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.
[0229] Examples of the coating resin and the matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, a straight-chain silicone resin containing an organic siloxane bond or a modified product thereof, a fluororesin, a polyester, a polycarbonate, a phenolic resin, an epoxy resin, and the like.
[0230] Furthermore, the coating resin and the matrix resin may contain other additives such as conductive particles.
[0231] Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0232] Here, in order to coat the surface of the core material with coating resin, a method of coating with a coating layer solution dissolved in a suitable solvent with coating resin and various additives added as required can be enumerated. As solvent, there is no particular limitation, and it is selectable considering the coating resin used, coating suitability, etc.
[0233] Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution, a spraying method in which the coating layer forming solution is sprayed onto the surface of the core material, a fluidized bed method in which the coating layer forming solution is sprayed while the core material is floated by flowing air, and a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and the solvent is removed.
[0234] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100.
[0235] [Example]
[0236] Hereinafter, the embodiments of the present invention will be described in detail by way of examples, but the embodiments of the present invention are not limited to these examples.
[0237] <Example 1>
[0238] CI Pigment Yellow 101 (manufactured by BASF, average particle size: 3 μm) was reduced in size as follows.
[0239] In the previous step, CI Pigment Yellow 101 was immersed in water containing 5% by mass of a surfactant (TAYCAPOWER BN2060, manufactured by Tayca Corporation) based on CI Pigment Yellow 101 to prepare a slurry having a solid concentration of 20%.
[0240] In the diameter reduction process, a continuous Key sand mill (KMC-3, manufactured by Inoue Seisakusho Co., Ltd.) was used. The conditions were: using high-purity alumina beads (TB-01 manufactured by Daming Chemical Industry Co., Ltd.) with a specific gravity of 3.9 and a bead diameter of 0.10 mm, setting the bead filling rate to 80% of the volume of the bead mill container, setting the peripheral speed of the stirring mechanism to 9.3 m / s, and implementing the diameter reduction until the average particle size reached 700 nm. After the diameter reduction was completed, the slurry was dried under reduced pressure to obtain powdered CI Pigment Yellow 101, which was measured and evaluated.
[0241] <Example 2>
[0242] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was 500 nm.
[0243] <Example 3>
[0244] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 250 nm.
[0245] <Example 4>
[0246] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 150 nm.
[0247] <Example 5>
[0248] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was 100 nm.
[0249] <Example 6>
[0250] The diameter reduction was carried out in the same manner as in Example 1 except that the beads used were glass beads having a specific gravity of 2.5 and a bead diameter of 0.10 mm (BZ-01 manufactured by AS ONE CO., LTD.).
[0251] <Example 7>
[0252] The diameter reduction was carried out in the same manner as in Example 1 except that the beads used were zirconia beads (YTZ-0.1 manufactured by NIKKATO CORPORATION) having a specific gravity of 6.0 and a bead diameter of 0.10 mm.
[0253] <Example 8>
[0254] The beads were reduced in diameter in the same manner as in Example 1 except that the beads used were stainless steel beads having a specific gravity of 7.6 and a bead diameter of 0.11 mm. The stainless steel beads having an average bead diameter of 0.11 mm were used by removing beads having a diameter of 90 μm or less from SUS304-150 manufactured by Fuji Seisakusho Co., Ltd. having a bead diameter of 125 to 45 μm using a 90 μm sieve.
[0255] <Example 9>
[0256] The diameter reduction was carried out in the same manner as in Example 1 except that the beads used were zirconia beads (YTZ-0.03 manufactured by NIKKATO CORPORATION) having a specific gravity of 6.0 and a bead diameter of 0.03 mm and that the bead mill apparatus was Easy Nano RMB (manufactured by AIMEX CORPORATION).
[0257] <Example 10>
[0258] The beads were reduced in diameter in the same manner as in Example 1 except that the beads used were high-purity alumina beads (TB-03 manufactured by Daimei Chemical Industry Co., Ltd.) having a specific gravity of 3.9 and a bead diameter of 0.30 mm.
[0259] <Example 11>
[0260] The beads were reduced in diameter in the same manner as in Example 1 except that the beads used were high-purity alumina beads (TB-04 manufactured by Daimei Chemical Industry Co., Ltd.) having a specific gravity of 3.9 and a bead diameter of 0.40 mm.
[0261] <Example 12>
[0262] The diameter reduction was carried out in the same manner as in Example 1 except that the peripheral speed of the stirring mechanism was set to 4.8 m / s.
[0263] <Example 13>
[0264] The diameter reduction was carried out in the same manner as in Example 1 except that the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0265] <Example 14>
[0266] The diameter reduction was carried out in the same manner as in Example 1 except that the bead mill was changed to Easy Nano RMB (manufactured by Amicus Corporation) and the peripheral speed of the stirring mechanism was changed to 15.0 m / s.
[0267] <Example 15>
[0268] The diameter reduction was carried out in the same manner as in Example 1 except that the beads used were zirconia beads (YTZ-0.3 manufactured by NIKKATO CORPORATION) having a specific gravity of 6.0 and a bead diameter of 0.30 mm and the peripheral speed of the stirring mechanism was 14.4 m / s.
[0269] <Example 16>
[0270] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the reduction was 250 nm and the beads used were glass beads having a specific gravity of 2.5 and a bead diameter of 0.10 mm (BZ-01 manufactured by Azowan Co., Ltd.).
[0271] <Example 17>
[0272] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the size reduction was 250 nm and the beads used were zirconia beads (YTZ-0.1 manufactured by NIKKATO CORPORATION) having a specific gravity of 6.0 and a bead diameter of 0.10 mm.
[0273] <Example 18>
[0274] The particle size reduction was carried out in the same manner as in Example 1, except that the average particle size after size reduction was set to 250 nm, the beads used were zirconia beads having a specific gravity of 6.0 and a bead diameter of 0.03 mm (YTZ-0.03 manufactured by NIKKATO Co., Ltd.), and the bead mill apparatus was set to Easy Nano RMB model (manufactured by Amicus Corporation).
[0275] <Example 19>
[0276] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the size reduction was 250 nm and the beads used were high-purity alumina beads (TB-03 manufactured by Daimei Chemical Industry Co., Ltd.) having a specific gravity of 3.9 and a bead diameter of 0.30 mm.
[0277] <Example 20>
[0278] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 250 nm and the peripheral speed of the stirring mechanism was set to 4.8 m / s.
[0279] <Example 21>
[0280] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 250 nm and the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0281] <Example 22>
[0282] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after size reduction was set to 250 nm, the beads used were zirconia beads (YTZ-0.3 manufactured by NIKKATO Co., Ltd.) having a specific gravity of 6.0 and a bead diameter of 0.30 mm, and the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0283] <Example 23>
[0284] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 250 nm and the bead filling rate was set to 70%.
[0285] <Example 24>
[0286] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the particle size reduction was set to 250 nm and the bead filling rate was set to 90%.
[0287] <Example 25>
[0288] The particle size reduction was carried out in the same manner as in Example 1 except that CI Pigment Yellow 101 used was from a different production lot (average particle size: 5 μm) from that of BASF Corporation and the average particle size after particle size reduction was 250 nm.
[0289] <Example 26>
[0290] The particle size reduction was carried out in the same manner as in Example 1 except that CI Pigment Yellow 101 manufactured by Neelikon (average particle size: 1 μm) was used and the average particle size after particle size reduction was 250 nm.
[0291] <Comparative Example 1>
[0292] The particle size reduction was carried out by high pressure dispersion using an impact disperser Altimizer (manufactured by Sugino Machinery Co., Ltd.) The slurry was prepared in the same manner as in Example 1 and the particle size reduction was carried out under 240 MPa until the average particle size reached 700 nm.
[0293] <Comparative Example 2>
[0294] The diameter reduction was carried out in the same manner as in Example 1 except that the beads used were zirconia beads (YTZ-0.4 manufactured by NIKKATO CORPORATION) having a specific gravity of 6.0 and a bead diameter of 0.40 mm, the bead mill apparatus was Easy Nano RMB model (manufactured by Amicus Corporation), and the peripheral speed of the stirring mechanism was set to 15.0 m / s.
[0295] <Comparative Example 3>
[0296] The diameter reduction was carried out in the same manner as in Example 1, except that the average particle diameter after diameter reduction was set to 250 nm and the beads used were stainless steel beads having a specific gravity of 7.6 and a bead diameter of 0.11 mm. The stainless steel beads having an average bead diameter of 0.11 mm were used by removing beads of 90 μm or less from SUS304-150 manufactured by Fuji Seisakusho Co., Ltd. having a bead diameter of 125 to 45 μm using a 90 μm sieve.
[0297] <Comparative Example 4>
[0298] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the size reduction was 250 nm and the beads used were high-purity alumina beads (TB-04 manufactured by Daimei Chemical Industry Co., Ltd.) having a specific gravity of 3.9 and a bead diameter of 0.40 mm.
[0299] <Comparative Example 5>
[0300] The particle size reduction was carried out in the same manner as in Example 1 except that the average particle size after the size reduction was set to 250 nm, the bead mill was set to Easy Nano RMB (manufactured by Amicus Corporation), and the peripheral speed of the stirring mechanism was set to 15.0 m / s.
[0301] <Measurement>
[0302] The following physical properties were measured for the CI Pigment Yellow 101 (after drying) after the diameter reduction obtained in the Examples and Comparative Examples according to the methods described above.
[0303] Average particle size
[0304] The diffraction angle 2θ of the peak in the X-ray diffraction pattern
[0305] <Evaluation>
[0306] The spectral reflectance of the reduced-diameter CI Pigment Yellow 101 (after drying) at 520 nm was measured using a spectrophotometer eXact (registered trademark) (manufactured by X-rite). Next, the fluorescent color of the reduced-diameter CI Pigment Yellow 101 was evaluated based on the spectral reflectance. The evaluation was performed based on the following criteria.
[0307] A: 110 or above
[0308] B: 90 or above
[0309] C: below 90
[0310] The results are shown in Table 1.
[0311] [Table 1-1]
[0312]
[0313] [Table 1-2]
[0314]
[0315] As can be seen from the results in Table 1, in this Example, CI Pigment Yellow 101 having a high fluorescent color even with a small diameter can be obtained compared with the comparative example.
[0316] Here, as an example, Figure 1 The figure shows CI Pigment Yellow 101 before diameter reduction (refer to Figure 1 (A)), CI Pigment Yellow 101 of the example after the diameter reduction (refer to Figure 1 (B)) and CI Pigment Yellow 101 of the comparative example after the diameter reduction (reference Figure 1 (C)) is an X-ray diffraction pattern obtained by powder X-ray diffraction.
[0317] like Figure 1 As shown, the CI Pigment Yellow 101 (refer to Figure 1 (B)) CI Pigment Yellow 101 of the comparative example after the diameter reduction (reference Figure 1 (C)) Each peak in the X-ray diffraction pattern is CI Pigment Yellow 101 before being reduced in diameter (refer to Figure 1 (A)) Not excessively displaced.
[0318] Thus, in this example, CI Pigment Yellow 101 having a high fluorescent color even with a small diameter was obtained compared with the comparative example.
[0319] <Examples 101 to 126>
[0320] Toners and developers using CI Pigment Yellow 101 of Examples 1 to 26 were prepared according to the following procedures.
[0321] -Preparation of CI Pigment Yellow 101 Dispersion-
[0322] In the diameter reduction step of Examples 1 to 26, a CI Pigment Yellow 101 dispersion having a solid content of 20% by mass was obtained from the CI Pigment Yellow 101 dispersion after the diameter reduction and before drying.
[0323] - Preparation of resin particle dispersion -
[0324] Terephthalic acid: 30 mol parts
[0325] Fumaric acid: 70 mol parts
[0326] Bisphenol A ethylene oxide adduct: 5 mol parts
[0327] Bisphenol A propylene oxide adduct: 95 mol parts
[0328] The above materials were prepared in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature was raised to 220°C in 1 hour. 1 part of tetraethyl titanate was added to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 230°C in 30 minutes. After the dehydration condensation reaction was continued at the temperature for 1 hour, the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,000 and a glass transition temperature of 60°C was obtained.
[0329] After adding 40 parts of ethyl acetate and 25 parts of 2-butanol as a mixed solvent into a container equipped with a temperature control unit and a nitrogen replacement unit, 100 parts of polyester resin are slowly added and dissolved, and a 10% by mass ammonia solution (equivalent to 3 times the amount in molar ratio relative to the acid value of the resin) is added thereto and stirred for 30 minutes. Next, the container is replaced with dry nitrogen, the temperature is maintained at 40°C, and 400 parts of deionized water are dripped at a rate of 2 parts / minute while stirring the mixed liquid. After the dripping is completed, it is returned to room temperature (20°C to 25°C), and bubbling is performed with dry nitrogen for 48 hours while stirring, thereby obtaining a resin particle dispersion in which ethyl acetate and 2-butanol are reduced to less than 1,000 ppm. Deionized water is added to the resin particle dispersion to adjust the solid content to 20% by mass to obtain a resin particle dispersion.
[0330] - Preparation of release agent particle dispersion -
[0331] Paraffin wax (HNP-9 manufactured by Nippon Seira Co., Ltd.): 100 parts
[0332] Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 1 part
[0333] Deionized water: 350 parts
[0334] The above materials are mixed and heated to 100°C, dispersed using a homogenizer (IKA, trade name ULTRA-TURRAX T50), and then dispersed using a Manton-Gaulin high-pressure homogenizer (Gaulin) to obtain a release agent particle dispersion (solid content 20 mass%) in which release agent particles with a volume average particle size of 200 nm are dispersed.
[0335] - Production of toner particles -
[0336] Resin particle dispersion: 400 parts
[0337] CI Pigment Yellow 101 Dispersion: 50 parts
[0338] Release agent particle dispersion: 25 parts
[0339] Anionic surfactant (Neogen RK, 20%): 10 parts
[0340] The above materials were placed in a round stainless steel flask, 0.1N (= mol / L) nitric acid was added and the pH was adjusted to 3.5, and then 30 parts of a nitric acid aqueous solution with a polyaluminium chloride concentration of 10% by mass was added. Then, after being dispersed at a liquid temperature of 30°C using a homogeniser (manufactured by IKA, trade name ULTRA-TURRAX T50), the mixture was heated to 45°C in a heating oil bath and maintained for 30 minutes. After that, 50 parts of the resin particle dispersion were added and maintained for 1 hour, 0.1N sodium hydroxide aqueous solution was added and the pH was adjusted to 8.5, and then heated to 84°C and maintained for 2.5 hours. Then, the mixture was cooled to 20°C at a rate of 20°C / min, the solid content was filtered out, and the mixture was fully washed with deionised water and dried to obtain toner particles. The volume average particle size of the toner particles was 5.8μm.
[0341] - Preparation of carrier -
[0342] Ferrite particles (average particle size 35 μm): 100 parts
[0343] Toluene: 14 parts
[0344] Polymethyl methacrylate (PMMA, weight average molecular weight 75,000): 5 parts
[0345] Carbon black: 0.2 parts (VXC-72, manufactured by Cabot Corporation, volume resistivity: 100 Ω·cm or less)
[0346] The above materials except the ferrite particles are dispersed in a sand mill to prepare a dispersion, and the dispersion is put into a vacuum degassing kneader together with the ferrite particles, and dried under reduced pressure while stirring to obtain a carrier.
[0347] - Production of toner -
[0348] 1.5 parts of hydrophobic silica (RY50 manufactured by Nippon Aerosil Co., Ltd.) and 1.0 parts of hydrophobic titanium oxide (T805 manufactured by Nippon Aerosil Co., Ltd.) were mixed with a sample mill at 10,000 rpm (revolutions per minute) for 30 seconds with respect to 100 parts of the obtained toner particles. Thereafter, the mixture was sieved with a vibrating sieve having a mesh size of 45 μm to prepare a toner. The volume average particle size of the obtained toner was 5.8 μm.
[0349] - Production of electrostatic image developer -
[0350] 8 parts of toner and 92 parts of carrier were mixed in a V mixer to prepare an electrostatic image developer.
[0351] <Evaluation (color development)>
[0352] The developers obtained in each example were evaluated and all showed excellent color development properties.
[0353] (Note) (((1)))
[0355] A CI Pigment Yellow 101, characterized in that:
[0356] having an average particle size of 100 nm or more and 700 nm or less,
[0357] In the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low-angle side exists in the range of the diffraction angle 2θ=11.66° or more and 11.86° or less. (((2)))
[0359] The CI Pigment Yellow 101 according to (((1))), which has an average particle size of 150 nm to 500 nm. (((3)))
[0361] The CI Pigment Yellow 101 according to (((1))) or (((2))), wherein, in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the third peak from the low-angle side exists in the range of a diffraction angle 2θ=17.86° or more and 18.06° or less. (((4)))
[0363] A method for producing the CI Pigment Yellow 101 described in any one of (((1))) to (((3))), comprising: using beads having a specific gravity of 2.5 to 6.0 and a bead diameter of 0.03 mm to 0.3 mm, and reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of 1 μm to 5 μm under the condition that the peripheral speed of a stirring mechanism is 4.8 m / s to 14.4 m / s. (((5)))
[0365] A coloring composition comprising the CI Pigment Yellow 101 described in any one of (((1))) to (((3))). (((6)))
[0367] The colored composition according to (((5))), wherein the colored composition is a toner for electrostatic charge image development.
[0368] The effects of the above method are as follows.
[0369] According to (((1))), there is provided a CI Pigment Yellow 101 having a higher fluorescent color even with a smaller diameter than the following CI Pigment Yellow 101: having an average particle diameter of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, a second peak from the low angle side exists in the range of a diffraction angle 2θ of less than 11.66° or more than 11.86°.
[0370] According to (((2))), there is provided a CI Pigment Yellow 101 having a high fluorescent color even when the diameter is small, compared with a case where the CI Pigment Yellow 101 has an average particle diameter of 100 nm or more and less than 150 nm or more than 500 nm and less than 700 nm.
[0371] According to (((3))), there is provided a CI Pigment Yellow 101 having a high fluorescent color even with a small diameter compared to the following case: in the case of CI Pigment Yellow 101, in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low angle side exists in the range of the diffraction angle 2θ=11.66° or more and 11.86° or less, and in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the third peak from the low angle side exists in the range of the diffraction angle 2θ less than 17.86° or more than 18.06°.
[0372] According to (((4))), there is provided a method for producing CI Pigment Yellow 101, wherein CI Pigment Yellow 101 has a high fluorescent color even when the diameter is small, compared with the following method for producing CI Pigment Yellow 101: comprising using beads having a specific gravity of less than 2.5 or more than 6.0 or a bead diameter of less than 0.03 mm or more than 0.3 mm, or reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of not less than 1 μm and not more than 5 μm under the condition that the peripheral speed of a stirring mechanism is less than 4.8 m / s or more than 14.4 m / s.
[0373] According to (((5))), a coloring composition is provided, which contains CI Pigment Yellow 101 having a high fluorescent color even when the diameter is small, compared with the case of using the following CI Pigment Yellow 101: having an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of diffraction angle 2θ less than 11.66° or more than 11.86°.
[0374] According to (((6))), a coloring composition is provided, which is a coloring agent for electrostatic image development and contains CI Pigment Yellow 101 having a high fluorescent color even when the diameter is small, compared with the case where the following CI Pigment Yellow 101 is used: having an average particle diameter of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side exists in the range of a diffraction angle 2θ of less than 11.66° or more than 11.86°.
Claims
1. A CI Pigment Yellow 101, characterized in that: having an average particle size of 100 nm or more and 700 nm or less, In the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low-angle side exists in the range of the diffraction angle 2θ=11.66° or more and 11.86° or less.
2. CI Pigment Yellow 101 according to claim 1, wherein The average particle size is 150 nm or more and 500 nm or less.
3. CI Pigment Yellow 101 according to claim 1 or 2, wherein In the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the third peak from the low-angle side exists in the range of the diffraction angle 2θ=17.86° or more and 18.06° or less.
4. A method for producing CI Pigment Yellow 101 according to any one of claims 1 to 3, characterized in that: include: CI Pigment Yellow 101 having an average particle size of 1 μm to 5 μm is reduced in size using beads having a specific gravity of 2.5 to 6.0 and a bead diameter of 0.03 to 0.3 mm at a peripheral speed of 4.8 to 14.4 m / s.
5. A coloring composition, characterized in that Contains the CI Pigment Yellow 101 according to any one of claims 1 to 3.
6. The coloring composition according to claim 5, wherein The coloring composition is a toner for developing electrostatic charge images.
Citation Information
Patent Citations
Insoluble azo pigment and colored composition
JP2004026930A